Modern foreign language learning: exploring the possible impact of parental experiences on student motivation. Issue 2 (15th March 2023) - Martin, Christopher
ABSTRACT: Purpose: This present paper draws on a doctoral study which provides an innovative insight into the extent to which parents influence their child's motivation to learn a foreign language. Methodology: An exploratory methodology was adopted to approach this study from multiple angles, using a sequential mixed-methods research design. A questionnaire, co-created by a professional community of practice, was administered to parents ( n  = 107) and children ( n  = 495) in four secondary schools in the wider West Midlands conurbation. This was followed by semi-structured dyadic interviews with six sets of parents and their children ( n  = 12). This gave a rounded view of parental orientations towards language learning and how this could impact their child's motivation. Findings: Quantitative analysis shows that there are strong, positive correlations between parent and child data for five of the six motivation constructs. Linear regression shows that parental level of general education has a statistically significant impact on four student motivation constructs. Results from the qualitative analysis show that parents were largely indifferent, with mixed experiences of language learning. Parents were also cognisant of issues surrounding the availability of different language options and possible timetabling constraints which impact the flexibility for children to choose a language. Originality: The present study is innovative through its inclusion of parental views towards learning a foreign language. Its research design paves the way for a widening of methodologies through the use of mixed methods to explore these orientations in greater detail as well as drawing on a professional community of practice as a partner in the research process.